PENGARUH POSISI SETENGAH DUDUK TERHADAP KENYAMANAN IBU PADA KALA II PERSALINAN DI PUSKESMAS KASSI-KASSI MAKASSAR - Nur Ismi Wahyuni; Sukmawati (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2021)
Objective: To determine the effect of the half-sitting position on maternal comfort in the second stage of labor in Kassi-Kassi Makassar Health Center in 2019. Method: The study was conducted in October 2019 at the Kassi-Kassi Makassar Health Center with the Quasi Experimental approach. The population in this study were all mothers who received a sample of 61 people with purposive sampling sampling. Results: The results of the study showed that of 61 respondents, who experienced maternal comfort at delivery as many as 49 people (80.3%) and those who were uncomfortable as many as 12 people (19.7%). The results showed that of the 61 respondents with maternal comfort in the second stage of labor after a half-sitting position as many as 49 respondents. While respondents who were uncomfortable at the second stage of labor were 12 respondents. Based on the results of statistical calculations using the Wilcoxon Signed Rank Test, the Z value of -2.138 was obtained with a value of p 0.004 <? 0.05. Discussion: The half-sitting position and delivery position are commonly applied in various hospitals or maternity clinics in Indonesia. This position requires the mother to sit with her back against the pillow, legs bent and thighs opened to the side. Conclusion: the conclusion of this study is that there is the influence of the half-sitting position on maternal comfort in the second stage of labor at the Kassi-Kassi Makassar Health Center. Suggestion: It is expected that the health center should provide more counseling to the mother so that the mother understands the position and comfort during delivery